Systemic tuberculosis with adrenal insufficiency: A forgotten presentation of a common disease - admin, César R. Carpio-Chanamé (2021)
A 47-year-old male with hyperpigmentation of the skin and oral mucosa, asthenia, nausea, vomiting, weight loss, abdominopelvic pain and hypotension. In addition, orchiepididymitis and scrotal fistula. In blood: hyponatremia, decreased plasma cortisol and elevated ACTH. Normal chest X-ray, negative smear.The tomography revealed increased dimensions in the right adrenal capsule and small adrenal nodules in the left. He underwent an orchiectomy and histopathology confirmed urogenital tuberculosis.The adrenal insufficiency was considered to be part of disseminated tuberculosis. The response to TB therapy was successful. This case is an unusual presentation of a common disease.